<< Chapter < Page Chapter >> Page >

We will use the example x 2 + 4 x + 1 = 0 to illustrate each step.

  1. Given a quadratic equation that cannot be factored, and with a = 1 , first add or subtract the constant term to the right sign of the equal sign.

    x 2 + 4 x = −1
  2. Multiply the b term by 1 2 and square it.

    1 2 ( 4 ) = 2 2 2 = 4
  3. Add ( 1 2 b ) 2 to both sides of the equal sign and simplify the right side. We have

    x 2 + 4 x + 4 = 1 + 4 x 2 + 4 x + 4 = 3
  4. The left side of the equation can now be factored as a perfect square.

    x 2 + 4 x + 4 = 3 ( x + 2 ) 2 = 3
  5. Use the square root property and solve.

    ( x + 2 ) 2 = ± 3 x + 2 = ± 3 x = −2 ± 3
  6. The solutions are −2 + 3 , and −2 3 .

Solving a quadratic by completing the square

Solve the quadratic equation by completing the square: x 2 3 x 5 = 0.

First, move the constant term to the right side of the equal sign.

x 2 3 x = 5

Then, take 1 2 of the b term and square it.

1 2 ( −3 ) = 3 2 ( 3 2 ) 2 = 9 4

Add the result to both sides of the equal sign.

x 2 3 x + ( 3 2 ) 2 = 5 + ( 3 2 ) 2 x 2 3 x + 9 4 = 5 + 9 4

Factor the left side as a perfect square and simplify the right side.

( x 3 2 ) 2 = 29 4

Use the square root property and solve.

( x 3 2 ) 2 = ± 29 4 ( x 3 2 ) = ± 29 2 x = 3 2 ± 29 2

The solutions are 3 2 + 29 2 , and 3 2 29 2 .

Got questions? Get instant answers now!
Got questions? Get instant answers now!

Solve by completing the square: x 2 6 x = 13.

x = 3 ± 22

Got questions? Get instant answers now!

Using the quadratic formula

The fourth method of solving a quadratic equation    is by using the quadratic formula    , a formula that will solve all quadratic equations. Although the quadratic formula works on any quadratic equation in standard form, it is easy to make errors in substituting the values into the formula. Pay close attention when substituting, and use parentheses when inserting a negative number.

We can derive the quadratic formula by completing the square    . We will assume that the leading coefficient is positive; if it is negative, we can multiply the equation by −1 and obtain a positive a . Given a x 2 + b x + c = 0 , a 0 , we will complete the square as follows:

  1. First, move the constant term to the right side of the equal sign:

    a x 2 + b x = c
  2. As we want the leading coefficient to equal 1, divide through by a :

    x 2 + b a x = c a
  3. Then, find 1 2 of the middle term, and add ( 1 2 b a ) 2 = b 2 4 a 2 to both sides of the equal sign:

    x 2 + b a x + b 2 4 a 2 = b 2 4 a 2 c a
  4. Next, write the left side as a perfect square. Find the common denominator of the right side and write it as a single fraction:

    ( x + b 2 a ) 2 = b 2 4 a c 4 a 2
  5. Now, use the square root property, which gives

    x + b 2 a = ± b 2 4 a c 4 a 2 x + b 2 a = ± b 2 4 a c 2 a
  6. Finally, add b 2 a to both sides of the equation and combine the terms on the right side. Thus,

    x = b ± b 2 4 a c 2 a

The quadratic formula

Written in standard form, a x 2 + b x + c = 0 , any quadratic equation can be solved using the quadratic formula    :

x = b ± b 2 4 a c 2 a

where a , b , and c are real numbers and a 0.

Given a quadratic equation, solve it using the quadratic formula

  1. Make sure the equation is in standard form: a x 2 + b x + c = 0.
  2. Make note of the values of the coefficients and constant term, a , b , and c .
  3. Carefully substitute the values noted in step 2 into the equation. To avoid needless errors, use parentheses around each number input into the formula.
  4. Calculate and solve.

Solve the quadratic equation using the quadratic formula

Solve the quadratic equation: x 2 + 5 x + 1 = 0.

Identify the coefficients: a = 1 , b = 5 , c = 1. Then use the quadratic formula.

x = ( 5 ) ± ( 5 ) 2 4 ( 1 ) ( 1 ) 2 ( 1 ) = 5 ± 25 4 2 = 5 ± 21 2
Got questions? Get instant answers now!
Got questions? Get instant answers now!

Questions & Answers

the gradient function of a curve is 2x+4 and the curve passes through point (1,4) find the equation of the curve
Kc Reply
1+cos²A/cos²A=2cosec²A-1
Ramesh Reply
test for convergence the series 1+x/2+2!/9x3
success Reply
a man walks up 200 meters along a straight road whose inclination is 30 degree.How high above the starting level is he?
Lhorren Reply
100 meters
Kuldeep
Find that number sum and product of all the divisors of 360
jancy Reply
answer
Ajith
exponential series
Naveen
what is subgroup
Purshotam Reply
Prove that: (2cos&+1)(2cos&-1)(2cos2&-1)=2cos4&+1
Macmillan Reply
e power cos hyperbolic (x+iy)
Vinay Reply
10y
Michael
tan hyperbolic inverse (x+iy)=alpha +i bita
Payal Reply
prove that cos(π/6-a)*cos(π/3+b)-sin(π/6-a)*sin(π/3+b)=sin(a-b)
Tejas Reply
why {2kπ} union {kπ}={kπ}?
Huy Reply
why is {2kπ} union {kπ}={kπ}? when k belong to integer
Huy
if 9 sin theta + 40 cos theta = 41,prove that:41 cos theta = 41
Trilochan Reply
what is complex numbers
Ayushi Reply
Please you teach
Dua
Yes
ahmed
Thank you
Dua
give me treganamentry question
Anshuman Reply
Solve 2cos x + 3sin x = 0.5
shobana Reply
Practice Key Terms 7

Get the best Algebra and trigonometry course in your pocket!





Source:  OpenStax, Algebra and trigonometry. OpenStax CNX. Nov 14, 2016 Download for free at https://legacy.cnx.org/content/col11758/1.6
Google Play and the Google Play logo are trademarks of Google Inc.

Notification Switch

Would you like to follow the 'Algebra and trigonometry' conversation and receive update notifications?

Ask